Consensus Development Project (CDP): An overview of staffing for safe and effective nursing care - Jane E. Ball; Peter Griffiths (Nursing Open, 2022)
Abstract We present an overview of the research evidence on nurse staffing levels in acute hospitals, and how it has been applied to policy and practice, focussing primarily on the UK. Drawing on research reviews and examples of specific studies, we outline the current state of knowledge. Much of the evidence comes from cross‐sectional studies. More recently, longitudinal studies allow a causal link between staffing and outcomes to be inferred. Lack of specificity on staffing levels has hindered application of research findings to practice; research rarely specifies how many nurses are needed for safe and effective care. The most significant impediment to achieving safe staffing has been an underestimation of the number of RNs needed and overestimation of the potential for substitution, resulting in low baseline staffing and a national shortage of RNs. Repeatedly, new staffing solutions are sought rather than tackle the problem of too few RNs head‐on.